2017
DOI: 10.1186/s40425-017-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell multiplexed cytokine profiling of CD19 CAR-T cells reveals a diverse landscape of polyfunctional antigen-specific response

Abstract: BackgroundIt remains challenging to characterize the functional attributes of chimeric antigen receptor (CAR)-engineered T cell product targeting CD19 related to potency and immunotoxicity ex vivo, despite promising in vivo efficacy in patients with B cell malignancies.MethodsWe employed a single-cell, 16-plex cytokine microfluidics device and new analysis techniques to evaluate the functional profile of CD19 CAR-T cells upon antigen-specific stimulation. CAR-T cells were manufactured from human PBMCs transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 40 publications
5
114
0
Order By: Relevance
“…Previous studies showed that the cytokine production profile of CAR T cells was highly diverse (2). As culturing T cells with different cytokines did not alter the relative distribution of CD29 + and CD29 -T cells, we propose to select for CD29 expression for the generation of highly toxic T cell products, in particular when donors have a low percentage of CD29 + T cells.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies showed that the cytokine production profile of CAR T cells was highly diverse (2). As culturing T cells with different cytokines did not alter the relative distribution of CD29 + and CD29 -T cells, we propose to select for CD29 expression for the generation of highly toxic T cell products, in particular when donors have a low percentage of CD29 + T cells.…”
Section: Discussionmentioning
confidence: 88%
“…Availability of multiplexed, single-cell approaches will greatly assist pre-infusion assessments of cellular immunotherapies, and these are now emerging. 100 The relevancy of readouts based on short-term effector functions to overall CAR-T potency is also questionable. Kunkele wileyonlinelibrary.com/jctb et al 107 demonstrated that CAR-T constructs that generated the highest activity in assays measuring specific lysis and cytokine secretion exhibited attenuated anti-tumour potency in vivo.…”
Section: In-process Control and Release Testingmentioning
confidence: 99%
“…In contrast, the cytokine profiles from single CAR-T cells that did not kill tumor cells showed no distinguishable grouping among these cytokines ( Figure 1g). A diverse landscape of antigen-specific response was observed in CD19-BB-3z CAR-T cells 13 . Their dominant polyfunctional cells also produce GranzymeB, GM-CSF, IL8, TNFa, IL13, and IFNg, in concordance with our observation in the third-generation CAR-T cells.…”
Section: Car Activation Leads To Heterogeneous Responses Involving a mentioning
confidence: 99%
“…Intra-cellular cytokine staining for flow cytometric analysis is not a true secretion assay and often leads to over-estimation of cytokine-secreting cells. Recently, Xue et al used single-cell multiplex cytokine profiling to measure the cytokine output of CD19-BB-3z CAR-T cells using CD19coated beads and revealed a diverse polyfunctional response upon activation 13 . However, the cytokine profile of a CAR-T cell is yet to be directly correlated to cytotoxicity, subtype and signaling in order to elucidate the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%